2007
DOI: 10.1016/j.ijgo.2007.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Complications of three sacrospinous ligament fixation techniques

Abstract: Passing the suture through the sacrospinous ligament under direct visualization may result in less intra and postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 16 publications
2
31
0
2
Order By: Relevance
“…According to Pollak et al the intra as well as post-operative complication were less with direct visualisation technique (2%) when compared to Dischamps clamp. 13 According to RCOG/BSUG joint guideline 1stJuly 2015, SSLF should be considered at the time of vaginal hysterectomy when the vault descends to the introitus during closure.…”
Section: Discussionmentioning
confidence: 99%
“…According to Pollak et al the intra as well as post-operative complication were less with direct visualisation technique (2%) when compared to Dischamps clamp. 13 According to RCOG/BSUG joint guideline 1stJuly 2015, SSLF should be considered at the time of vaginal hysterectomy when the vault descends to the introitus during closure.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate of 92-97% in literature. [6][7][8][9] All patients in this series were included following disease specific validated quality of life questionnaires, assessment of symptoms and impact of the condition and examination is made according to quantifying tools such as POPQ. Assessment for stress incontinence was done in partially full bladder after reducing the prolapse with sponge holder.…”
Section: Resultsmentioning
confidence: 99%
“…Placing the sutures at an arbitrary fixed point (1.5-2.0 cm) medial to the ischial spine could not be justified. Pollak et al (2007) compared the complications of the techniques used to pass suture through Sacrospinous Ligament (SSL), concluded that passing the suture through SSL under direct visualization may result in less intra and postoperative complications. 8 There is an increase in incidence of anterior vaginal wall prolapse following SSLF due to exaggerated retroversion of vagina.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…techniques have been suggested over the years to overcome these problems [11]. Some surgeons elected to implant meshes for the reinforcement of the weakened and herniated pelvic floor.…”
Section: Introductionmentioning
confidence: 99%